ANALYSIS THE AFFECT OF PROFITABILITY, ASSET GROWTH AND COMPANY SIZE TO THE CAPITAL STRUCTURE OF PROPERTY AND REAL ESTATE COMPANIES - Soewignyo, Tonny (JBE (Journal of Business and Economics), 2013)
Capital structure is the proportion between uses of debt to equity. In specifying optimal, we must consider many things influencing it. This research was to analyze the factors that influence the company capital structures. The sample of this research consisting of 35 property and real estate companies that listed on Indonesian Stock Exchange for the period 2010-2011. This study uses simple linear regression method to see the contribution of each variable in influence capital structure. The empirical result indicates that profitability, asset growth and company size affect significantly positive  to the capital structure. The outcome of this study is to provide property & real estate companies a guide regarding capital structure. Capital structure is a policy for every company in which the factors influencing the decision making will differ for each company.